Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Verify that the equation $y''+y'-xy=0$ has a three-term, recursion formula and find its series solutions $y_1$ and $y_2$ such that

$a)$ $y_1(0)=1$, $y_1'(0)=0$;

$b)$ $y_2(0)=0$, $y_2'(0)=1$.

Using the following theorem, of which it guarantees that both series converge at ever $x\in \mathbb{R}$, let $\displaystyle\sum_{j=0}^{ \infty } a_j$ and $\displaystyle\sum_{j=0}^{ \infty } b_j$ be two absolutely converfent series which converge to limits $\alpha$ and $\beta$, respectively. Define the seies as $\displaystyle\sum_{j=0}^{ \infty } c_m$ with summands $c_m=\displaystyle\sum_{n=0}^{ m } a_j\cdot b_{m-j}$. Then the series $\displaystyle\sum_{m=0}^{ \infty } c_m$ converges to $\alpha \cdot \beta$.

share|improve this question
1  
What have you tried? This is very similar to this other question you just posted, which you seemed to be able to get started on. –  Antonio Vargas Dec 11 '12 at 3:19
    
I'm mainly not sure what it's asking. –  Purply.Platypus Dec 11 '12 at 3:21
add comment

1 Answer 1

Let $y=\sum\limits_{n=0}^\infty a_nx^n$ ,

Then $y'=\sum\limits_{n=0}^\infty na_nx^{n-1}=\sum\limits_{n=1}^\infty na_nx^{n-1}$

$y''=\sum\limits_{n=1}^\infty n(n-1)a_nx^{n-2}=\sum\limits_{n=2}^\infty n(n-1)a_nx^{n-2}$

$\therefore\sum\limits_{n=2}^\infty n(n-1)a_nx^{n-2}+\sum\limits_{n=1}^\infty na_nx^{n-1}-x\sum\limits_{n=0}^\infty a_nx^n=0$

$\sum\limits_{n=2}^\infty n(n-1)a_nx^{n-2}+\sum\limits_{n=1}^\infty na_nx^{n-1}-\sum\limits_{n=0}^\infty a_nx^{n+1}=0$

$\sum\limits_{n=2}^\infty n(n-1)a_nx^{n-2}+\sum\limits_{n=2}^\infty(n-1)a_{n-1}x^{n-2}-\sum\limits_{n=3}^\infty a_{n-3}x^{n-2}=0$

$a_1+2a_2+\sum\limits_{n=3}^\infty(n(n-1)a_n+(n-1)a_{n-1}-a_{n-3})x^{n-2}=0$

$\therefore\begin{cases}a_1+2a_2=0\\n(n-1)a_n+(n-1)a_{n-1}-a_{n-3}=0\end{cases}$

$\therefore y''+y'-xy=0$ has a three-term recursion formula.

However, when we really to solve it, we will not handle directly the above recursion formula as it is too complicated to solve it.

So we will try this approach:

Let $y=e^{ax}u$ ,

Then $y'=e^{ax}u'+ae^{ax}u$

$y''=e^{ax}u''+ae^{ax}u'+ae^{ax}u'+a^2e^{ax}u=e^{ax}u''+2ae^{ax}u'+a^2e^{ax}u$

$\therefore e^{ax}u''+2ae^{ax}u'+a^2e^{ax}u+e^{ax}u'+ae^{ax}u-xe^{ax}u=0$

$e^{ax}u''+(2a+1)e^{ax}u'+(a^2+a-x)e^{ax}u=0$

$u''+(2a+1)u'+(a^2+a-x)u=0$

Choose $a=-\dfrac{1}{2}$ , the ODE becomes $u''-\left(x+\dfrac{1}{4}\right)u=0$

Let $u=\sum\limits_{n=0}^\infty b_n\left(x+\dfrac{1}{4}\right)^n$ ,

Then $u'=\sum\limits_{n=0}^\infty nb_n\left(x+\dfrac{1}{4}\right)^{n-1}=\sum\limits_{n=1}^\infty nb_n\left(x+\dfrac{1}{4}\right)^{n-1}$

$u''=\sum\limits_{n=1}^\infty n(n-1)b_n\left(x+\dfrac{1}{4}\right)^{n-2}=\sum\limits_{n=2}^\infty n(n-1)b_n\left(x+\dfrac{1}{4}\right)^{n-2}$

$\therefore\sum\limits_{n=2}^\infty n(n-1)b_n\left(x+\dfrac{1}{4}\right)^{n-2}-\left(x+\dfrac{1}{4}\right)\sum\limits_{n=0}^\infty b_n\left(x+\dfrac{1}{4}\right)^n=0$

$\sum\limits_{n=2}^\infty n(n-1)b_n\left(x+\dfrac{1}{4}\right)^{n-2}-\sum\limits_{n=0}^\infty b_n\left(x+\dfrac{1}{4}\right)^{n+1}=0$

$\sum\limits_{n=2}^\infty n(n-1)b_n\left(x+\dfrac{1}{4}\right)^{n-2}-\sum\limits_{n=3}^\infty b_{n-3}\left(x+\dfrac{1}{4}\right)^{n-2}=0$

$2b_2+\sum\limits_{n=3}^\infty(n(n-1)b_n-b_{n-3})\left(x+\dfrac{1}{4}\right)^{n-2}=0$

$\therefore\begin{cases}2b_2=0\\n(n-1)b_n-b_{n-3}=0\end{cases}$

$\begin{cases}b_2=0\\b_n=\dfrac{b_{n-3}}{n(n-1)}\end{cases}$

$\therefore\begin{cases}b_0=b_0\\b_{3n}=\dfrac{b_0}{(2\times3)(5\times6)(8\times9)......((3n-1)3n)}\forall n\in\mathbb{N}\\b_1=b_1\\b_{3n+1}=\dfrac{b_1}{(3\times4)(6\times7)(9\times10)......(3n(3n+1))}\forall n\in\mathbb{N}\\b_{3n+2}=0~\forall n\in\mathbb{Z}^*\end{cases}$

$\begin{cases}b_0=b_0\\b_{3n}=\dfrac{(4\times7\times10\times......(3n+1))b_0}{2\times3\times4\times5\times6\times7\times8\times9\times10\times......(3n-1)3n(3n+1)}\forall n\in\mathbb{N}\\b_1=b_1\\b_{3n+1}=\dfrac{(2\times5\times8\times......(3n-1))b_1}{2\times3\times4\times5\times6\times7\times8\times9\times10\times......(3n-1)3n(3n+1)}\forall n\in\mathbb{N}\\b_{3n+2}=0~\forall n\in\mathbb{Z}^*\end{cases}$

$\begin{cases}b_0=b_0\\b_{3n}=\dfrac{\biggl(\prod\limits_{k=1}^n(3k+1)\biggr)b_0}{(3n+1)!}\forall n\in\mathbb{N}\\b_1=b_1\\b_{3n+1}=\dfrac{\biggl(\prod\limits_{k=1}^n(3k-1)\biggr)b_1}{(3n+1)!}\forall n\in\mathbb{N}\\b_{3n+2}=0~\forall n\in\mathbb{Z}^*\end{cases}$

$\begin{cases}b_{3n}=\dfrac{\biggl(\prod\limits_{k=0}^n(3k+1)\biggr)b_0}{(3n+1)!}\forall n\in\mathbb{Z}^*\\b_1=b_1\\b_{3n+1}=\dfrac{\biggl(\prod\limits_{k=1}^n(3k-1)\biggr)b_1}{(3n+1)!}\forall n\in\mathbb{N}\\b_{3n+2}=0~\forall n\in\mathbb{Z}^*\end{cases}$

$\therefore y=C_1e^{-\frac{x}{2}}\sum\limits_{n=0}^\infty\dfrac{\biggl(\prod\limits_{k=0}^n(3k+1)\biggr)\left(x+\dfrac{1}{4}\right)^{3n}}{(3n+1)!}+C_2e^{-\frac{x}{2}}\biggl(x+\dfrac{1}{4}+\sum\limits_{n=1}^\infty\dfrac{\biggl(\prod\limits_{k=1}^n(3k-1)\biggr)\left(x+\dfrac{1}{4}\right)^{3n+1}}{(3n+1)!}\biggr)$

$y'=C_1e^{-\frac{x}{2}}\biggl(\sum\limits_{n=1}^\infty\dfrac{3n\biggl(\prod\limits_{k=0}^n(3k+1)\biggr)\left(x+\dfrac{1}{4}\right)^{3n-1}}{(3n+1)!}-\sum\limits_{n=0}^\infty\dfrac{\biggl(\prod\limits_{k=0}^n(3k+1)\biggr)\left(x+\dfrac{1}{4}\right)^{3n}}{2(3n+1)!}\biggr)+C_2e^{-\frac{x}{2}}\biggl(\dfrac{7}{8}-\dfrac{x}{2}+\sum\limits_{n=1}^\infty\dfrac{\biggl(\prod\limits_{k=1}^n(3k-1)\biggr)\left(x+\dfrac{1}{4}\right)^{3n}}{(3n)!}-\sum\limits_{n=1}^\infty\dfrac{\biggl(\prod\limits_{k=1}^n(3k-1)\biggr)\left(x+\dfrac{1}{4}\right)^{3n+1}}{2(3n+1)!}\biggr)$

For $y_1$ , $C_1$ and $C_2$ are the solution of $\begin{cases}C_1\sum\limits_{n=0}^\infty\dfrac{\prod\limits_{k=0}^n(3k+1)}{4^{3n}(3n+1)!}+C_2\biggl(\dfrac{1}{4}+\sum\limits_{n=1}^\infty\dfrac{\prod\limits_{k=1}^n(3k-1)}{4^{3n+1}(3n+1)!}\biggr)=1\\C_1\biggl(\sum\limits_{n=1}^\infty\dfrac{3n\prod\limits_{k=0}^n(3k+1)}{4^{3n-1}(3n+1)!}-\sum\limits_{n=0}^\infty\dfrac{\prod\limits_{k=0}^n(3k+1)}{2^{6n+1}(3n+1)!}\biggr)+C_2\biggl(\dfrac{7}{8}+\sum\limits_{n=1}^\infty\dfrac{\prod\limits_{k=1}^n(3k-1)}{4^{3n}(3n)!}-\sum\limits_{n=1}^\infty\dfrac{\prod\limits_{k=1}^n(3k-1)}{2^{6n+3}(3n+1)!}\biggr)=0\end{cases}$

For $y_2$ , $C_1$ and $C_2$ are the solution of $\begin{cases}C_1\sum\limits_{n=0}^\infty\dfrac{\prod\limits_{k=0}^n(3k+1)}{4^{3n}(3n+1)!}+C_2\biggl(\dfrac{1}{4}+\sum\limits_{n=1}^\infty\dfrac{\prod\limits_{k=1}^n(3k-1)}{4^{3n+1}(3n+1)!}\biggr)=0\\C_1\biggl(\sum\limits_{n=1}^\infty\dfrac{3n\prod\limits_{k=0}^n(3k+1)}{4^{3n-1}(3n+1)!}-\sum\limits_{n=0}^\infty\dfrac{\prod\limits_{k=0}^n(3k+1)}{2^{6n+1}(3n+1)!}\biggr)+C_2\biggl(\dfrac{7}{8}+\sum\limits_{n=1}^\infty\dfrac{\prod\limits_{k=1}^n(3k-1)}{4^{3n}(3n)!}-\sum\limits_{n=1}^\infty\dfrac{\prod\limits_{k=1}^n(3k-1)}{2^{6n+3}(3n+1)!}\biggr)=1\end{cases}$

share|improve this answer
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.